2016
DOI: 10.1080/15562948.2016.1180470
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Refugee Empowerment(s) in Resettlement Organizations

Abstract: Abstract:In-depth interviews with both organizational staff and refugee-clients in two American refugee resettlement organizations explore how empowerment is communicated to and understood by refugees being "empowered." This study found that while organizational staff professed empowerment focused on self-sufficiency as self-determination, in practice their communication to clients defined self-sufficiency a priori in economic terms. Refugee-clients instead constructed empowerment(s) in economic, educational, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…They are often gatekeepers of resources, such as information and social networks, to which refugees need access in order to seek employment (Godin and Renaud 2002; Lacroix et al . 2015; Steimel 2017).…”
Section: Organizational‐level Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…They are often gatekeepers of resources, such as information and social networks, to which refugees need access in order to seek employment (Godin and Renaud 2002; Lacroix et al . 2015; Steimel 2017).…”
Section: Organizational‐level Factorsmentioning
confidence: 99%
“…Similarly, Nawyn (2010, p. 157) suggested that training offered by support organizations was not only inadequate and led to particular ethnically stereotypical occupations, such as manicurists, but also ‘funnelled refugee women into feminized occupations’, including childcare providers. As such, support organizations can limit refugees’ career choices by offering immediately available jobs and failing to cast a wide net for employment opportunities (Steimel 2017). Often, support organizations are forced to enact the political agenda of (local) governments, which prioritizes immediate employment over career planning and professional advancement (Finnan 1982).…”
Section: Organizational‐level Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…NSOs are generally acknowledged to play a critical role in the general resettlement process and workforce integration (Godin and Renaud, 2002; Lacroix et al, 2015; Steimel, 2016, 2017). Previous studies identify several challenges in NSO support, including: a lack of organized programs (Korac, 2003); support providers’ lack of experience and expertise; an absence of individually customized assistance (Godin and Renaud, 2002); inappropriate funding structures that curtail NSOs’ flexibility to provide services and create unhealthy competition within the sector (Mukhtar et al, 2016); and employment rules and regulations associated with funding programs that favor immediate economic outcomes but limit refugees’ future career choices (Steimel, 2017). Further, some research points to discrepancies in refugees’ expectations of support and NSOs’ offerings (Makwarimba et al, 2013; Steimel, 2017; Stewart et al, 2012; Torezani et al, 2008), the perceived expertise of staff (Steimel, 2016), and the quality of programs (Agbényiga et al, 2012).…”
Section: Literature Review: Nsos and Refugee Workforce Integrationmentioning
confidence: 99%
“…Previous studies identify several challenges in NSO support, including: a lack of organized programs (Korac, 2003); support providers’ lack of experience and expertise; an absence of individually customized assistance (Godin and Renaud, 2002); inappropriate funding structures that curtail NSOs’ flexibility to provide services and create unhealthy competition within the sector (Mukhtar et al, 2016); and employment rules and regulations associated with funding programs that favor immediate economic outcomes but limit refugees’ future career choices (Steimel, 2017). Further, some research points to discrepancies in refugees’ expectations of support and NSOs’ offerings (Makwarimba et al, 2013; Steimel, 2017; Stewart et al, 2012; Torezani et al, 2008), the perceived expertise of staff (Steimel, 2016), and the quality of programs (Agbényiga et al, 2012). These studies highlight the difficulties facing NSOs, often small organizations with limited capacity, in the grand challenge of resettling refugees.…”
Section: Literature Review: Nsos and Refugee Workforce Integrationmentioning
confidence: 99%